Note about the divinity *Besencla (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
The recent rediscovery of two Roman votive altars lacking explicit theonymic identification—yet commissioned by the same dedicator responsible for a third altar dedicated to the indigenous deity Besencla—raises the question of whether all three were offerings to the same divinity. In addition, an alternative interpretation of the theonym is proposed: Ceseticia.
Keywords: Acculturation; Divinities; Lusitania; *Besencla; Ceseticia